Practical reinforcement learning : develop self-evolving, intelligent agents with OpenAI Gym, Python, and Java /: develop self-evolving, intelligent agents with OpenAI Gym, Python, and Java. (2017) - Akhtar, Farrukh S. M
No abstract available